Shepherds in Morocco: the invisible people of sheep and goat systems - Nassif F.; El Amiri B. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
In Morocco, the 2013-2017 average of sheep population is 19,290,628 heads and that of goats is 5,817,801. The number of sheep farms is 781,563 and the number of goat farms stands at 301,897. The people responsible for tending these animals are overlooked. Available scientific literature on shepherds is scanty. This paper aims at analyzing the current situation of shepherds and prospects of the shepherding profession. It is based on exploitation of census data and semi-structured interviews with at least five shepherds in each of the following provinces: Agadir Ida-Ou-Tanan, Azilal, Berrechid, Chichaoua, El Kelâa des Sraghna, Essaouira, Khouribga, Rhamna, Safi, Settat, Taroudant, Tata and Youssoufia. According to the 1971 population census, the total number of shepherds was 283,900, over half of which are aged less than 15 years of age. The population of shepherds decreased by 82% between 1971 and the 2014 censuses. The less than 15 years category has disappeared in the 2004 and 2014 censuses. The female contribution to shepherding stands at 17% in the 1971 and 2014 censuses while it reached 25% in the 2004 census. Shepherds form heterogeneous groups in terms of social status, working conditions, remuneration forms and salary levels. The rural young people do not reject to work as shepherds unreasonably, they refuse the conditions associated with the activity. When shepherding is conducted within the family farm it goes unpaid and when it is assumed for others, it results in low pay, long hours, unbearable working conditions and unequal social relations. The shepherding activity needs social and legal recognition, upgrading through professionalization and enhanced attractiveness of the work.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)